1996
DOI: 10.1139/v96-057
|View full text |Cite
|
Sign up to set email alerts
|

An AM1 calculational study of the protonation and reactions of 3,4-dihydro-2-oxo-1,4-ethanoquinoline, 3,4-dihydro-2-oxo-1,4-propanoquinoline, 3,3,4,5-tetrahydro-2-oxo-1,5-ethanobenzazepine, 3,3,4,5-tetrahydro-2-oxo-1,5-propanobenzazepine, and N-methyl-4-bromo-2-methylacetanilide

Abstract: Abstract:The gas phase N-and 0-protonation of distorted amides 3,4-dihydro-2-0x0-1.4-ethanoquinoline (la), 3,4-dihydro-2-0x0-l,4-propanoquinoline (lb), 3,3,4,5-tetrahydro-2-0x0-1,5-ethanobenzazepine (lc), and 3,3,4,5-tetrahydro-2-0x0-1,5-propanobenzazepine (16) and normal amides 4-bromo-2,N-dimethylacetanilide (5a) and 2,N-dimethylacetanilide (Sb), along with the N-protonation of benzoquinuclidine (7), has been studied calculationally at the semiempirical level of theory with AM 1. Calculated enthalpies of N-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 13 publications
2
13
0
Order By: Relevance
“…Some insight into the question of N- vs. O-protonation has been provided by Brown and Wang (Scheme ). 59a,b Their observations are in line with our predictions of N-protonation of the 3̄.2.2 system and O-protonation of the 3̄.3.2 system. Brown is careful to note that it is not clear whether these very slow reactions are under kinetic or thermodynamic control.…”
Section: Resultssupporting
confidence: 88%
“…Some insight into the question of N- vs. O-protonation has been provided by Brown and Wang (Scheme ). 59a,b Their observations are in line with our predictions of N-protonation of the 3̄.2.2 system and O-protonation of the 3̄.3.2 system. Brown is careful to note that it is not clear whether these very slow reactions are under kinetic or thermodynamic control.…”
Section: Resultssupporting
confidence: 88%
“…451 Using DFT calculations, Greenberg predicted that related bridged lactams display higher electron density at nitrogen as compared to planar amides. 70,71 Recently, Greenberg reported that protonation of the relatively undistorted 1-azabicyclo[3.3.1]nonan-2-one also proceeds at nitrogen (Scheme 122).…”
Section: Reactivity Of Bridged Lactams and Related Heterocyclesmentioning
confidence: 99%
“…Some examples of sterically hindered amides were reported [ 70 , 71 , 72 ] to exhibit moderately low amidicity and carbonylicity values. One representative example is 21 , where the amide functionality is sterically hindered and, hence, distorted.…”
Section: Discussionmentioning
confidence: 99%